The association between duration of breastfeeding and atopy in children with or without family history of atopic disease - Riana Novy; Budi Setiabudiawan; Cissy B. Kartasasmita (Indonesian Pediatric Society, 2007)
Background Atopic diseases (AD) are the most common chronicdiseases in childhood, and their incidence has a tendency to increaserecently. Tendency to have atopy could be triggered by many factorsoriginated in early life, including time of breastfeeding cessation.Objective To determine the association between exclusive andduration of breastfeeding and atopy in children with or withoutfamily history of atopic disease.Methods This was an observational clinical epidemiology studyperformed at Babakansari, Padasuka, Garuda Primary Health CareCenter in Bandung from January to March 2006. One hundredfifty of 749 children were randomized from group with and withoutfamily history of AD. They underwent skin prick tests and totalserum IgE level analysis. Atopy was defined as a positive skinprick test to any of the eight allergens tested. History of exclusiveand duration of breastfeeding was obtained from their parents.Significance tests for contingency tables were on the basis of x 2test for association odds ratio with 95% confidence interval.Results Atopy was found in 28.2% of children, of whom 32.4% withand 23.9% without family history of AD. Children exclusivelybreastfed exhibited a reduced risk of atopy (5.8% v 35.3%, OR=0.11,95%CI= 0.03;0.34, P<0.001). The difference of atopy was stronglysignificant between children who had exclusive breastfeeding andthose without exclusive breastfeeding whether or not the subjectshad family history of AD (P<0.001). There was a highly significantrisk reduction for atopy related to prolonged breastfeeding (=6months) (OR=0.37, 95%CI = 0.19 to 0.72, P=0.001). Thedifference of atopy was strongly significant between children whohad prolonged breastfeeding and short breastfeeding duration whetheror not the subjects had family history of AD (P<0.001)Conclusions Exclusive and prolonged breastfeeding decrease atopyin children with as well as without family history of AD.